(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mathematics is in all walks of life from the worlds of business and technology, to the sciences, to medicine, and even to environmental and management. Very few research studies have been conducted in mathematical creativity and writing to learn mathematics students who are conventional in thought and readily conform to the school norms are considered better for academic tasks and they are creative students who were seen as threats and became challenging for teachers. In this study the investigator has attempted to study the influences of various demographic variables like gender, localityand medium of instruction. The researcher adopted normative survey method. 500 students of IX standard from 8 schools in Salem District were selected as sample by stratified random sampling technique. Characteristics of creative thinking in mathematics scale constructed by Renzulhi, J.S et.al (2004). This contained 40 items. Its reliability value was 0.80. Writing to learn mathematics scale constructed by Edel Mary Reilly (2007). This contained 20 items on 3 dimensions. A reliability co - efficient of 0.84 was obtained using split half method. Quantitative data analysis was done. Results shows that IX Standard Boys and Girls do not differ in mathematical characteristics, creative characteristics and characteristics of the potentially creative thinking in mathematics and IX Standard rural and urban students do not differ in their Mathematics in general, writing in math class, Math teacher.